2007
DOI: 10.1007/s00432-007-0328-4
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic importance of DNA repair gene polymorphisms of XRCC1 Arg399Gln and XPD Lys751Gln in lung cancer patients from India

Abstract: These findings suggest that genetic polymorphisms in the DNA repair genes may modulate overall lung cancer susceptibility and that pathological stage and XRCC1 Arg399Gln independently predicted overall survival among Indian lung cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
41
0
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 40 publications
8
41
0
4
Order By: Relevance
“…Therefore, the allele G and genotype GG may be contribute to play a protection from lung cancer in Chinese, and could be a useful molecular biomarker for assessing the risk of lung cancer. The XRCC1 c.1178G>A genetic polymorphism might be linked to other non-synonymous polymorphisms, such as Arg194Trp, Arg280His, Arg399Gln in XRCC1 gene, which have been approved to associate with the risk of lung cancer (Giachino et al, 2007;Lopez-Cima et al, 2007;Sreeja et al, 2008;Chang et al, 2009;Kalikaki et al, 2009;Butkiewicz et al, 2011;Qian et al, 2011;Chen et al, 2012;. These genetic variants might influence the expression and function of XRCC1 proteins in BER pathway, which has been approved to be associated with lung cancer risk (Hao et al, 2006;Giachino et al, 2007;Lopez-Cima et al, 2007;Sreeja et al, 2008;Kalikaki et al, 2009; .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the allele G and genotype GG may be contribute to play a protection from lung cancer in Chinese, and could be a useful molecular biomarker for assessing the risk of lung cancer. The XRCC1 c.1178G>A genetic polymorphism might be linked to other non-synonymous polymorphisms, such as Arg194Trp, Arg280His, Arg399Gln in XRCC1 gene, which have been approved to associate with the risk of lung cancer (Giachino et al, 2007;Lopez-Cima et al, 2007;Sreeja et al, 2008;Chang et al, 2009;Kalikaki et al, 2009;Butkiewicz et al, 2011;Qian et al, 2011;Chen et al, 2012;. These genetic variants might influence the expression and function of XRCC1 proteins in BER pathway, which has been approved to be associated with lung cancer risk (Hao et al, 2006;Giachino et al, 2007;Lopez-Cima et al, 2007;Sreeja et al, 2008;Kalikaki et al, 2009; .…”
Section: Discussionmentioning
confidence: 99%
“…However, the exact mechanism of lung cancer remains poorly understood. Recently, many studies have investigated the association of lung cancer with genetic polymorphisms of human X-ray repair cross-complementing group 1 (XRCC1) gene in different populations (Hao et al, 2006;Giachino et al, 2007;Lopez-Cima et al, 2007;Sreeja et al, 2008;Chang et al, 2009;Kalikaki et al, 2009;Wang et al, 2009;Butkiewicz et al, 2011;Huang et al, 2011;Li et al, 2011;PerezMorales et al, 2011;Qian et al, 2011;Rybarova et al, 2011;Chen et al, 2012;Cui et al, 2012;Dai et al, 2012;Karkucak et al, 2012;Ke et al, 2012;Li et al, 2012;Huang et al, 2013;Letkova et al, 2013;Natukula et al, 2013;Ouyang et al, 2013;Sun et al, 2013;Wu et al, 2013;. The XRCC1 proteins play important roles in DNA base excision repair (BER) pathway which may be influence the development of lung cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies reported that the human X-ray repair complementing group 1 (XRCC1) gene is one of the most important candidate genes for influencing susceptibility to lung cancer (Hao et al, 2006;Giachino et al, 2007;López-Cima et al, 2007;Sreeja et al, 2008;Chang et al, 2009;Kalikaki et al, 2009;Wang et al, 2009;Yin et al, 2009a,b;Butkiewicz et al, 2011;Li et al, 2011;Qian et al, 2011;Chen et al, 2012;Cui et al, 2012;Guo et al, 2013). The potential associations between lung cancer and multiple genetic variants of XRCC1 in different populations have been reported (Hao et al, 2006;Giachino et al, 2007;López-Cima et al, 2007;Improta et al, 2008;Sreeja et al, 2008;Chang et al, 2009;Kalikaki et al, 2009;Yin et al, 2009a,b;Butkiewicz et al, 2011;Qian et al, 2011;Cui et al, 2012;Guo et al, 2013). Several genetic variants, including arginine (Arg) 194 tryptophan (Trp), Arg 280 histidine (His) and Arg399 glutamine (Gln), were significantly associated with the susceptibility to lung cancer (Giachino et al, 2007;López-Cima et al, 2007;Sreeja et al, 2008;Kalikaki et al, 2009;Yin et al, 2009a,b;Butkiewicz et al, 2011;Qian et al, 2011;Guo et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…DNA repair genes, such as xeroderma pigmentosum group D (XPD) and X-ray repair cross-complementing group 1 (XRCC1), have roles in genomic stability via DNA repair pathways, like nucleotide excision repair, base excision repair and double-strand break repair (Sreeja et al 2008;López-Cima et al 2007). Gene polymorphisms may occur at codon 194, 280 and 399 for XRCC1 whereas they may occur at codon 312 and 751 for XPD.…”
Section: Introductionmentioning
confidence: 99%